Work-Life Balance and Performance: The Mediating Role of Job Satisfaction at BPS North Maluku - Muhammad Mansur, Iman; Hasyim, Abdul Wahab; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study analyzes the influence of work-life balance on employee performance with job satisfaction as a mediating variable among employees of the Central Bureau of Statistics (BPS) in North Maluku Province. Using a quantitative approach, data were collected from 100 millennial and Generation Z employees through a structured questionnaire and analyzed using hierarchical regression in SPSS 25. The results show that work-life balance has a positive and significant effect on job satisfaction and employee performance. Job satisfaction also positively and significantly improves employee performance and partially mediates the relationship between work-life balance and performance. These findings indicate that employees who maintain a balanced work and personal life tend to experience higher job satisfaction, which subsequently enhances their performance. The study highlights the importance of organizational policies that support work-life balance to strengthen well-being and productivity within public sector institutions.